Barriers and Facilitators to Implementing the HEADS-ED: A Rapid Screening Tool for Pediatric Patients in Emergency Departments. Issue 12 (December 2017) - MacWilliams, Kate; Curran, Janet; Racek, Jakub; Cloutier, Paula; Cappelli, Mario
Abstract : Objectives: This study sought to identify barriers and facilitators to the implementation of the HEADS-ED, a screening tool appropriate for use in the emergency department (ED) that facilitates standardized assessments, discharge planning, charting, and linking pediatric mental health patients to appropriate community resources. Methods: A qualitative theory-based design was used to identify barriers and facilitators to implementing the HEADS-ED tool. Focus groups were conducted with participants recruited from 6 different ED settings across 2 provinces (Ontario and Nova Scotia). The Theoretical Domains Framework was used as a conceptual framework to guide data collection and to identify themes from focus group discussions. Results: The following themes spanning 12 domains were identified as reflective of participants' beliefs about the barriers and facilitators to implementing the HEADS-ED tool: knowledge, skills, beliefs about capabilities, social professional role and identity, optimism, beliefs about consequences, reinforcement, environmental context and resources, social influences, emotion, behavioral regulation and memory, and attention and decision process. Conclusions: The HEADS-ED has the potential to address the need for better discharge planning, complete charting, and standardized assessments for the increasing population of pediatric mental health patients who present to EDs. This study has identified potential barriers and facilitators, which should be considered when developing an implementation plan for adopting the HEADS-ED tool into practice within EDs.